Efficacy of azilsartan medoxomil in patients with hypertension and stable coronary artery disease in combination with type 2 diabetes - A. M. Kochergina; O. L. Barbarash (Рациональная фармакотерапия в кардиологии)
Aim. To study the effect of azilsartan medoxomil (AZL-M) on the 24-hour blood pressure (BP) profile in patients with hypertension (HTN), type 2 diabetes (T2D) and stable coronary artery disease (CAD).Material and methods.  A total of 183 patients with CAD in combination with HTN and T2D took part in the study (100 men (54,64%), 83 women (45,36%)). All patients were previously prescribed a statin, antiplatelet therapy, a beta-blocker, and an angiotensin-converting enzyme inhibitor (ACEI) or angiotensin receptor blocker (ARB). At baseline,  the proportion of people taking ARBs and ACEIs was 30% and 70%, respectively. All study participants were discontinued from a previously prescribed ARBs or ACE inhibitors and were prescribed 6-month AZL-M (Edarbi®) therapy. During this period, according to the study plan, patients visited the medical center to assess the effectiveness and safety of therapy and blood pressure changes.Results. The mean age of the patients was 65,0 years (60-69  years), while the mean body mass index (BMI) — 31,24 kg/m2. The mean age of female participants was higher than the mean age of males: 66,35±6,59 vs 62,72±8,82 years (p=0,002). The mean BMI in women was higher and was 33.08 kg/m2, while in men it was 30,74 kg/m2 (p=0,001). Six-month  AZL-M therapy decreased 24-hour BP values. Thus, the time index of systolic blood pressure (SBP) hypertension in the daytime decreased from 63% to 12%, while at night from 70% to 10%, and the time index of diastolic blood pressure (DBP) hypertension  in the daytime from 18% to 10%, and at night from 44% to 8%. The main result is confirmation of AZL-M effectiveness in relation to BP control, as well as good drug tolerability. At the visit after 1-month AZL-M therapy, target BP values  were recorded in 45,4%  of participants, and after six months — the proportion of people with normal 24-hour BP values was 69,9%.Conclusion. Edarbi® therapy in patients with HTN in combination with T2D and stable CAD leads  to 24-hour BP normalization. At the same time, the drug has a good safety profile, since the reported adverse events were not related to the drug.